Structural, ultrastructural and immunohistochemical evidence of testosterone effects and its ablation on the bulbourethal gland of the Artibeus planirostris bat (Chiroptera, Mammalia) - Puga, Cíntia C.I. [UNESP]; Beguelini, Mateus R.; Morielle-Versute, Eliana [UNESP]; Vilamaior, Patricia S.L. [UNESP]; Taboga, Sebastião R. [UNESP] (Elsevier, 2017)
This study evaluated the effects of testosterone in the bulbourethral glands (BG) of the bat, Artibeus planirostris, by performing castration and posterior hormonal supplementation of the animals. The results showed a decrease in testosterone levels in animals 15 days after castration, which induced a small reduction in epithelium height, percentage of AR+ cells, and an increase in the amount of basal cells. This reduction became more severe in groups castrated for longer periods (19 and 22 days), where there was also an increase in apoptotic cells. Moreover, the hormonal supplementation increased testosterone levels (after 3 and 7 days of supplementation), causing a glandular reactivation that increased the epithelium height and AR expression. In conclusion, BG took longer to respond to ablation of testosterone than other reproductive glands, since it showed evident aspects of regression only in animals 22 days after castrated.
Keywords: Bat; Bulbourethral gland; Castration; Hormone supplementation; Testosterone